The Role of the Boarding School System on Leadership Character Building and 21st Century Skills in High School Students at Global Islamic Boarding School South Kalimantan - Iman Ahmad Gymnastiar; Achmad Hufad; Sri Wahyuni (Universitas Pendidikan Indonesia, 2023)
Boarding school is considered an effective educational environment to shape leadership character and 21st century skills in high school students. The boarding school system at Global Islamic Boarding School South Kalimantan allows students to live and learn in a controlled and structured environment. This allows students to focus on their education without the distraction of the outside environment. In addition, students are given the opportunity to develop social and leadership skills through various organized activities. This study aims to investigate the role of the boarding school system in shaping leadership character and 21st century skills in high school students at Global Islamic Boarding School South Kalimantan. The research method used is qualitative with a Participatory Observation approach. Data were collected through interviews with students, teachers, and staff at the school, as well as observations of daily activities at the school. The results of this study indicate that the boarding school system at Global Islamic Boarding School South Kalimantan is very effective in shaping leadership character and 21st century skills in high school students. Students learn to live independently, manage their time well, and complete their assignments on time. They are also taught social and leadership skills. In addition, students also learn to use technology effectively and responsibly.